ANALISIS TAHANAN ISOLASI PADA ISOLATOR PORSELIN DAN POLIMER TERHADAP POLUTAN GARAM DI GISTET 500 KV ADIPALA CILACAP - Agam Celvano Darmadi; Kholistainingsih Kholistianingsih; Priyono Yulianto (Fakultas Teknik, Universitas Wijayakusuma Purwokerto, 2022)
GISTET 500 kV Adipala is one of the locations that is in the spotlight in the Central Java Transmission Main Unit (UIT JBT) because of frequent pollutant problems, especially during the dry season. This causes the surrounding air to have a high salt content and also the flyash from the PLTU. This condition causes the insulators on the tower and gantry to be exposed to pollutants and can result in flashover and breakdown. This study discusses the effectiveness of polymer insulators by testing the insulation resistance of clean porcelain insulators, polluted porcelain, clean polymers, and polluted polymers. To get the condition of the insulator polluted with salt water, the method of raining on the insulator is carried out. The result of the clean porcelain test was 2970 GOhm. in the experiment with polluted porcelain insulators, the following results were obtained: the minimum 50ml experiment measured a resistance value of 2950 GOhm, which was reduced by 1% from the clean one and the maximum 500ml experiment measured the resistance value to 390,3 GOhm, which was 87% reduced from the clean one. The net polymer insulator test results are 3222.8 GOhm. In the experiment with polluted polymer insulators, the following results were obtained: the minimum 50ml experiment measured a resistance value of 2982 GOhm, which was 7% less, the maximum 500ml experiment was 2382.8 GOhm, 26% less. From the results of these experiments, it can be seen that in the porcelain insulator experiment with salt water polluted, the insulation resistance value decreased in each experiment until the maximum experiment was 500ml which obtained a resistance value of 390.3 GOhm. The results of the clean polymer insulator test were 3222.8 GOhm, while the pollutant polymer insulator experiment recorded a value that was not significantly decreased with the lowest value in the 500ml experiment of 2382.8 GOhm. When compared with the minimum standard of insulation resistance for the 500 kV system used by PLN is 500 MOhm. Porcelain insulators that experience continuous exposure to pollutants have the potential to experience flashover and faster breakdown compared to polymer insulators when viewed from the trend of decreasing insulating resistance. It can be concluded that polymer insulators are more effective for use in environments that have a high level of exposure to air pollution such as at GISTET Adipala. Keywords: Porcelain Insulator, Polymer Insulator, Pollutant, Flashover, Breakdown GISTET 500 kV Adipala adalah salah satu lokasi yang menjadi sorotan di Unit Induk Transmisi Jawa Bagian Tengah (UIT JBT) karena seringnya masalah polutan terutama pada musim kemarau. Hal ini menyebabkan udara sekitar memiliki kandungan garam yang tinggi dan juga flyash dari PLTU. GISTET Adipala. Hal ini menyebabkan isolator pada tower dan gantry menjadi terpapar polutan dan dapat mengakibatkan terjadinya flashover dan breakdown. Oleh karena itu diperlukan analisis efektifitas isolator polimer dengan cara melakukan pengujian tahanan isolasi terhadap isolator porselin bersih, porselin berpolutan, polimer bersih, dan polimer berpolutan. Untuk mendapatkan kondisi isolator berpolutan air garam, dilakukan metode penghujanan ke arah isolator. Hasil pengujian porselin bersih tercatat 2970 GOhm. pada percobaan isolator porselin berpolutan didapat hasil sebagai berikut: percobaan 50ml, terukur nilai tahanan sebesar 2950 GOhm, yaitu berkurang 1% dan percobaan 500ml terukur nilai tahanan sebesar 390,3 GOhm, yaitu berkurang 87%. Untuk hasil pengujian isolator polimer bersih sebesar 3222,8 GOhm. 50ml terukur nilai tahanan sebesar 2982 GOhm, yaitu berkurang 7%, 500ml yaitu sebesar 2382,8 GOhm, berkurang 26% dari yang bersih. Dari hasil percobaan tersebut dapat dilihat pada percobaan isolator porselin berpolutan air garam adalah nilai tahanan isolasi yang menurun pada tiap percobaan hingga percobaan paling banyak yaitu 500ml yang diperoleh nilai tahanan 390,3 GOhm. Hasil pengujian isolator polimer bersih sebesar 3222,8 GOhm, sementara percobaan isolator polimer berpolutan tercatat nilai yang tidak begitu turun dengan nilai paling rendah pada percobaan 500ml sebesar 2382,8 GOhm. Jika dibandingkan dengan Standar minimal tahanan isolasi untuk sistem 500 kV yang digunakan PLN adalah 500 MOhm. Isolator porselin yang mengalami paparan polutan secara terus menerus berpotensi mengalami flashover dan breakdown lebih cepat dibandingkan dengan isolator polimer jika dilihat dari trend penurunan tahanan isolasinya. Dapat disimpulkan bahwa Isolator polimer lebih efektif untuk digunakan pada lingkungan yang memiliki tingkat paparan polusi udara yang tinggi seperti di GISTET Adipala. Kata Kunci: Isolator porselin, Isolator Polimer, Polutan, Flashover, Breakdown